Climate governance in international and comparative perspective : issues and experiences in Africa, Latin America, and the Caribbean - Haruna, Peter Fuseini; El Baradei, Laila; Van Jaarsveldt, Liza Ceciel; Benavides, Abraham D.; Stanica, Cristina M. (Public administration & social equity., 2024)
"This book pulls literature together to examine the quality of climate governance based in the experience of Global South regions-Africa, Latin America, and Caribbean. While these regions are resilient, the IPCC 2022 Report indicates that the effects of climate change are crippling their thinly structured governance systems and limited capacities. For example, in addition to environmental devastation, loss of life, and livelihoods, these regions have endured most of the "loss and damage" due to climate change impacts. How are they responding? What are the outcomes? And where do they go from here? Given this background, the book's goal is to question assumptions about climate governance patterns, systems, institutions, and processes in these regions, using comparative analytical techniques while distilling information about policy outcomes that other approaches do not provide. It argues that these regions and individual countries within them have a lot to learn from and about each other rather than look to the Global North and wealthy countries for economic, political, and administrative models that hardly match their lived experience and ontological outlooks. In doing so, it aspires to promote a fruitful South-South policy-related dialogue via scholarly exchanges and also contribute to advance the study and practice of international and comparative public administration. From this perspective, scholars, researchers, educators, public managers, and practitioners will find the book relevant to and useful for their respective endeavors"--